Analisis perundangan dan kes hibah amanah di Malaysia - Mohd Zamro Muda,; Nurnazirah Rosdi,; Noor Lizza Mohamed Said, (Penerbit Universiti Kebangsaan Malaysia, 2023)
The tendency of the Muslim community in property planning to use hibah products is increasing. This situation caused Islamic banking and financial institutions as well as companies and estate planning agencies to take the opportunity by introducing various hibah products, among them trust hibah. The trust hibah is a combination of the principles of hibah and trust. If observed in more detail, the trust hibah is formed through two contracts, namely the hibah contract and the trust contract. Since the trust hibah is a combination of the principles of hibah and trust, it has given rise to legal controversy because the issue of hibah is under the State jurisdiction and the issue of trust is under the Federal jurisdiction. Jurisdiction conflicts in trust hibah matters will continue and certainly confusion regarding the exclusive jurisdiction of the Syariah Court in cases related to Muslim property will continue to exist. Thus, this article aims to identify the jurisdiction of the Federal and State in relation to the trust hibah and to examine the cases of trust hibah that have been decided by the Civil Court and Shariah Court. This study is a qualitative study which utilises documents analysis approach in its data collection process. The study found that there are various forms of judgment in the trial of cases related to the trust hibah. Therefore, the parties involved, especially the legislative body, need to resolve this matter by creating a legal enactment or a guideline that is monitored by an authoritative body. This study has an impact on agencies that are directly involved with wealth planning, legal practitioners, the judiciary and further to the community who are competent to choose a trust hibah contract as their wealth planning instrument.